Towards rational fiscal incentives (good investments or wasted gifts?) - Renato E. Reside (University of the Philippines, School of Economics (UPSE), 2006)
This study is literally about missing tax revenues. In an environment of declining public school quality and student test scores, classroom, textbook and teacher shortages, inadequate supplies of public health facilities, roads and ports, not to mention shortfalls in tax collections, where did the missing tax revenues that could be used to finance these really go? A large part of the answers can be found in this study.
Keywords: 330